A public health strategy for e-cigarettes - Schneider, Sven; Diehl, Katharina (Wiener klinische Wochenschrift, 2015)
The e-cigarette may present a new and significant Public Health problem: Studies published so far do not seem to indicate that e-cigarette use is just a passing trend. If e-cigarette use is less harmless than it is portrayed in many advertisements, Public Health would do well to start a serious discussion about a suitable prevention policy as soon as possible.The aim of this short paper is to discuss a range of measures designed to prevent e-cigarette consumption.Concretely, we suggest to monitor e-cigarette use, the e-cigarette industry and prevention policies, to implement a vapor-free policy, to develop help to quit e-cigarette use, to inform about the health risks of e-cigarette use, to establish regulations on e-cigarette advertising, promotion and sponsorship, and to introduce taxes on e-cigarettes.